A National Survey on Peri-interventional Management of Percutaneous Transhepatic Biliary Drainage. Issue 4 (August 2017) - Pek, Chulja J.; van Dijk, Monique; Groot Koerkamp, Bas; Moelker, Adriaan; van Eijck, Casper H.J.
Abstract : Purpose: The purpose of this study is to evaluate knowledge about management of percutaneous transhepatic biliary drainage (PTBD) catheters among nurses taking care of hepato-pancreato-biliary (HPB) patients. Methods: Six HPB nurses from the Dutch national HPB association created a questionnaire that was complemented by 2 HPB surgeons, 3 HPB interventional radiologists, and a methodologist. Registered nurses working at the department of gastroenterology or gastrointestinal surgery and familiar with the care for HPB patients were invited to complete the questionnaire. Results: In total 120 completed questionnaires from Dutch nurses were returned. The responders were working in 38 of 64 different hospitals. About half of the respondents considered their own knowledge insufficient, which was reflected in the response to the specific questions concerning the PTBD procedure, and 70% rated the knowledge of their immediate nursing colleagues as insufficient. Less than 50% of the respondents knew whether antibiotic-prophylaxis or "pain medication" was required before PTBD procedure. Only a few respondents were aware of the existence of a hospital protocol for PTBD management and its content. Conclusions: Nursing care for biliary catheters is not standardized nationwide, and consensus on management is lacking. An evidence-based guideline for PTBD management is advised for nursing care of patients with HPB diseases.